2001
DOI: 10.1051/0004-6361:20010687
|View full text |Cite
|
Sign up to set email alerts
|

An optical inverse-Compton hotspot in 3C 196?

Abstract: Abstract. Several hotspots of FRII radio sources have previously been detected in the X-ray at a flux level consistent with the X-rays being due to inverse-Compton scattering of radio "synchrotron photons synchrotron self-Compton", if the magnetic fields in the hotspots are close to their equipartition values. However, the number of hotspots compact and bright enough to exhibit detectable X-ray emission is small, so it is worth searching for synchrotron self-Compton emission in the optical, in spite of the obv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Cygnus A, γ min ∼ 300-400 (Carilli et al 1991;Lazio et al 2006;Hardcastle 2001); 3C295, γ min ∼ 800 (Harris et al 2000;Hardcastle 2001); 3C123, γ min ∼ 1000 Hardcastle 2001); PKS 1421−490, γ min ∼ 650 (this work). Leahy et al (1989) presented evidence for a low-energy cutoff in two other hot spots: 3C268.1 and 3C68.1.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Cygnus A, γ min ∼ 300-400 (Carilli et al 1991;Lazio et al 2006;Hardcastle 2001); 3C295, γ min ∼ 800 (Harris et al 2000;Hardcastle 2001); 3C123, γ min ∼ 1000 Hardcastle 2001); PKS 1421−490, γ min ∼ 650 (this work). Leahy et al (1989) presented evidence for a low-energy cutoff in two other hot spots: 3C268.1 and 3C68.1.…”
Section: Introductionmentioning
confidence: 61%
“…In both these objects, the hotspot radio spectra are significantly flatter between 150 MHz and 1.5 GHz than they are above 1.5 GHz, which suggests a similar value of γ min to those listed above, provided the hotspot magnetic field strengths are similar. More recently, Hardcastle (2001) reported on a possible detection of an optical inverse Compton hot spot in the quasar 3C196. By modeling the synchrotron self-Compton (SSC) emission and assuming a magnetic field strength close to the equipartition value, they inferred a cutoff Lorentz factor γ min ∼ 500.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of detected X-ray hot spots is interesting in itself, given that calculations based on SSC emission at equipartition suggested that only the few brightest hot spots would be detected with Chandra (e.g., Hardcastle 2001). In order to assess quantitatively the extent to which the new detections conflict with an SSC model, we decided to fit a simple SSC model to all the hot spots and determine the ratio between the observed and predicted flux densities.…”
Section: Modeling and Resultsmentioning
confidence: 99%
“…The fact that a synchrotron model can be fitted through the radio, optical, and X-ray points in some high-R sources would have to be a coincidence in an SSC model, although this is a weak constraint; the optical emission might also be SSC, as it is thought to be in a couple of low-R sources (Hardcastle 2001;Brunetti 2002).…”
Section: þmentioning
confidence: 99%
“…Specifically, the minimum Lorentz factor of this electron energy distribution is related to the luminosity as L rad ∝ γ min s−2 (Equation 8 of . The minimum Lorentz factor in the hotspot has been estimated by other authors for selected radio sources including: Cygnus A (McKean et al 2016), PKS 1421-490 (Godfrey et al 2009), 3C123, 3C196 and 3C295 (Hardcastle 2001). These hotspot Lorentz factor estimates are mostly in the order of a few hundred although these estimates are quite uncertain due to the confounding effects of free-free and synchrotron selfabsorption.…”
Section: Minimum Electron Lorentz Factormentioning
confidence: 99%